Boosting Fast Sodium Ion Storage by Synergistic Effect of Heterointerface Engineering and Nitrogen Doping Porous Carbon Nanofibers. Issue 13 (12th February 2022) - Zhang, Qi; Zeng, Yaping; Ling, Changsheng; Wang, Liu; Wang, Zhiyong; Fan, Tian‐E; Wang, Heng; Xiao, Jianrong; Li, Xinyu; Qu, Baihua
Abstract: Heterointerface engineering with multiple electroactive and inactive supporting components is considered an efficient approach to enhance electrochemical performance for sodium‐ion batteries (SIBs). Nevertheless, it is still a challenge to rationally design heterointerface engineering and understand the synergistic effect reaction mechanisms. In this paper, the two‐phase heterointerface engineering (Sb2 S3 and FeS2 ) is well designed to incorporate into N‐doped porous hollow carbon nanofibers (Sb‐Fe‐S@CNFs) by proper electrospinning design. The obtained Sb‐Fe‐S@CNFs are used as anode in SIBs to evaluate the electrochemical performance. It delivers a reversible capacity of 396 mA h g –1 after 2000 cycles at 1 A g –1 and exhibits an ultra‐long high rate cycle life for 16 000 cycles at 10 A g –1 . The admirable electrochemical performance is mainly attributed to the following reasons: The porous carbon nanofibers serve as an accelerator of the electrons/ions and a buffer to alleviate volume expansion upon long cyclic performance. The abundant phase boundaries of Sb2 S3 /FeS2 exert low Na + adsorption energy and greatly promote the charge transfer in the internal electric field calculated by first‐principle density functional theory. Therefore, the as‐prepared Sb‐Fe‐S@CNFs represents a promising candidate for an efficient anode electrode material in SIBs. Abstract : The two‐phase heterointerface engineering (Sb2 S3 and FeS2 ) is well designed to incorporate into N‐doped porous hollow carbon nanofibers (Sb‐Fe‐S@CNFs) by proper electrospinning design. The obtained Sb‐Fe‐S@CNFs delivers an ultra‐long high rate cycle life for 16 000 cycles at 10 A g ‐1 .